Nilai-Nilai Pendidikan Hindu dalam Epos Ramayana - Oktavia, Anatasya Fitri (Satya Widya: Jurnal Studi Agama, 2025)
This study aims to analyze the Hindu educational values contained in the Ramayana epic by Valmiki, one of the most significant classical texts in the Hindu tradition. The Ramayana presents moral, ethical, and spiritual teachings that form the foundation of human character development. This research employs a qualitative method using content analysis of the Ramayana text, particularly the sections related to the actions and dialogues of the main characters such as Rama, Sita, Lakshmana, Bharata, and Hanuman. The findings indicate that Hindu educational values in the Ramayana include dharma (truth and moral duty), bhakti (loyalty and devotion), tapasya (self-restraint and spiritual discipline), satya (honesty), and leadership values grounded in wisdom and justice. These values are represented through the exemplary moral and spiritual behavior of the central characters. Furthermore, the educational values in the Ramayana remain relevant for strengthening modern character education, as they offer a universal ethical framework that can be integrated into learning processes. This study is expected to contribute to the development of Hindu education studies and promote the use of classical texts as sources of moral instruction and character formation. Keywords: Ramayana, Hindu education, dharma, bhakti, character